ANALISA KEBIJAKAN OTONOMI DESA DAN DESENTRALISASI FISKAL MENURUT UU NO. 6 TAHUN 2014 TENTANG DESA: Evaluasi, Implementatif Dan Implikasi Fiskal Pada Desa-Desa Di Kecamatan Pataruman, Kota Banjar, Jawa Barat - Sriono, Basuki (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Decentralization refers to the distribution of authority from the Central Government to Local Governments to manage governance and public administration, with the aim of improving public services and achieving equitable development. Transfers to Regions (TKD) are funds sourced from the State Budget (APBN) and constitute part of state expenditures allocated and distributed to regional governments/villages to be managed in financing governmental affairs under their authority in supporting governance implementation. Village Funds are part of Transfers to Regions intended to support the financing of village governance, development implementation, community empowerment, and community development, with the objective of improving village community welfare and quality of human life. The Allocation of Village Funds is part of the balancing funds received by regencies/municipalities, amounting to at least 10 percent (ten percent) of the General Allocation Fund and Revenue Sharing Fund received by regencies/municipalities in the regional budget. The enactment of Law Number 6 of 2014 concerning Villages has provided legal recognition of the existence of villages, placing Village Governments in a strategic role and position in public service delivery and community empowerment. This study is conducted using a normative juridical perspective with a statutory approach and analysis of village financial reports, aiming to identify benchmarks for the successful management of the Village Revenue and Expenditure Budget (APBDes) as reviewed from the Village Law and fiscal policy.